One for all: cobalt-containing polymethacrylates for magnetic ceramics, block copolymerization, unexpected electrochemistry, and stimuli-responsiveness. Issue 5 (5th January 2016) - Rüttiger, C.; Pfeifer, V.; Rittscher, V.; Stock, D.; Scheid, D.; Vowinkel, S.; Roth, F.; Didzoleit, H.; Stühn, B.; Elbert, J.; Ionescu, E.; Gallei, M.
Abstract : Functional cobalt-containing homo and block polymers are probed with respect to their redox-induced switchability and as preceramic materials. Abstract : Novel cobalt-containing homo- and diblock copolymers with poly(methyl methacrylate) (PMMA) are synthesized by atom transfer radical polymerization (ATRP) of a neutral cobalt-complex methacrylate. An efficient route for a single-step synthesis of the cobalt precursor based on easily-available starting materials followed by esterification with methacrylic acid is presented. The cobalt-methacrylate monomer is furthermore polymerized by thermal, free radical and statistical copolymerization with MMA and investigated with respect to (absolute) molar masses, polymer composition, and thermal properties. ATRP affords block copolymers as evidenced by 1 H NMR spectroscopy, size exclusion chromatography (SEC) and differential scanning calorimetry (DSC). The cobalt-containing homopolymers are investigated and tailored with respect to their thermal conversion into magnetic cobalt oxides and elemental cobalt which is evidenced by X-ray diffraction (XRD), Raman spectroscopy, and superconducting quantum interference device (SQUID) magnetometry measurements. The (reversible) electrochemistry of the cobalt-containing polymethacrylates and block copolymers thereof are thoroughly addressed by cyclic voltammetry (CV) studies. Interestingly, the prepared metalloblock copolymers exhibit redox-responsiveness (both reduction and oxidation) and thus structure formation in the presence of a reduction or oxidation reagent are demonstrated by transmission electron microscopy (TEM).